Предмет: Алгебра,
автор: Герффинс
Помогите пожалуйста
Преобразуйте алгебраическое выражение в многочлен стандартного вида :
3(2-x)²-(2x²+x-5)(x²-2)+(x²+4)(4-x²)
Спасибо за ранее!)
Ответы
Автор ответа:
0
3x^4(2-x)²-(2x²+x-5)(x²-2)+(x²+4)(4-x²)=
=3(4-4x+x^2)- (2x^4+x^3-5x^2-4x^2-2x+10)+16-x^4=
=12-12x+3x^2-2x^4-x^3+9x^2+2x-10+16-x^4=
=-3x^4-x^3+12x^2-10x+18
=3(4-4x+x^2)- (2x^4+x^3-5x^2-4x^2-2x+10)+16-x^4=
=12-12x+3x^2-2x^4-x^3+9x^2+2x-10+16-x^4=
=-3x^4-x^3+12x^2-10x+18
Похожие вопросы
Предмет: Право,
автор: seliametovaelviza
Предмет: Обществознание,
автор: tanni68
Предмет: Українська мова,
автор: bogdanasolonovic
Предмет: Математика,
автор: Pro100Olesa